2017
DOI: 10.1080/14494035.2017.1320854
|View full text |Cite
|
Sign up to set email alerts
|

Governance change and governance learning in Europe: stakeholder participation in environmental policy implementation

Abstract: Current European Union (EU) policies require policy-makers on different levels of government to engage with new forms of governance such as participatory planning, aiming to improve environmental policy delivery. We address the central issue of how policy-makers learn about the appropriateness of different modes of governance. By way of example, we examine recent innovations in EU water governance -primarily through the enactment of the Water Framework Directive (2000) and the Floods Directive (2007), and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Co-creation dynamics to match demand, funding and supply Based on the results, the themes addressed by policymakers' and herders' knowledge demands, supply of science and available funding match significantly more between the time period 2009-2018 than 2000-2009 ( Figure 3). The change seems to be in line with general tendencies in environmental policy and governance to change from hierarchical top-down approaches towards participatory governance (Challies et al, 2017). In research, the movement towards the co-creation of knowledge approaches with an emphasis on societally relevant research, are bridging the gap (Nilsson et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…Co-creation dynamics to match demand, funding and supply Based on the results, the themes addressed by policymakers' and herders' knowledge demands, supply of science and available funding match significantly more between the time period 2009-2018 than 2000-2009 ( Figure 3). The change seems to be in line with general tendencies in environmental policy and governance to change from hierarchical top-down approaches towards participatory governance (Challies et al, 2017). In research, the movement towards the co-creation of knowledge approaches with an emphasis on societally relevant research, are bridging the gap (Nilsson et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…This requirement has implications both in terms of coordination across administrative levels at different geographical scales of the RBD and for cross-sectoral coordination among different water-use sectors that must align their interests and objectives to improve the state of the water bodies [3,16]. In the same vein, the WFD links the achievement of effective policy implementation to public participation [4,17,18]. For instance, participatory planning is supposed to improve the quality of river basin planning, as expert-based and local knowledge are included in the decision-making processes, as well as to increase social acceptance towards decisions that should, in turn, facilitate implementation.…”
Section: River Basin Planning Under the Eu Water Framework Directivementioning
confidence: 99%
“…For this purpose, two targets were set in 2000: first, preventing further deterioration of water bodies, and second, improving their state with the aim of achieving 'good water status' by 2015 (Article 4, WFD). As a 'framework' directive, the WFD does not prescribe EU countries what to do to improve water quality and management but rather tell them how to do it [4][5][6]. In particular, the WFD establishes the river basin planning process as the 'central tool' to achieve water quality objectives [7].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research has found that participation by civil society as a stakeholder in environmental issues leads to better environmental decision-making (Challies et al 2017;Reed 2008;Newig and Fritsch 2009;Charnley and Engelbert 2005). Although some scholars point out that participation by civil society can, in certain conditions, lead to negative effects (Newig et al 2018).…”
Section: Introductionmentioning
confidence: 99%